Mechanisms of SiO oxidation: Implications for dust formation - Andersson, Stefan; Gobrecht, David; Valero, Rosendo (Frontiers in Astronomy and Space Sciences, 2023)
Rate coefficients of gas-phase oxidation and clustering reactions of SiO, Si2O2 and Si2O3 have been calculated using master equation calculations based on density functional theory calculations. These reactions have been postulated to initiate efficient formation of silicate dust particles in outflows around dying (AGB) stars. Both OH radicals and H2O molecules can be present in these environments and their reactions with SiO and the smallest SiO cluster, Si2O2, affect the efficiency of eventual dust formation. The calculations show that the reactions involving OH are fast. Reactions involving H2O are not efficient routes to oxidation but may under the right conditions lead to hydroxylated species. The reaction of Si2O2 with H2O, which has been suggested as efficient producing Si2O3, is therefore not as efficient as previously thought. If H2O molecules dissociate to form OH radicals, oxidation of SiO and dust formation could be accelerated. Kinetics simulations of oxygen-rich circumstellar environments using our proposed reaction scheme suggest that under typical conditions only small amounts of SiO2 and Si2O2 are formed and that most of the silicon remains as molecular SiO.